PELESTARIAN NILAI KEARIFAN LOKAL MELALUI KESENIAN REOG KENDANG DI TULUNGAGUNG - Nurmaning, Bina Andari (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
All regions in Indonesia almost own the value of local wisdom, and it's just that, in reality, it is infrequent to find local knowledge that is empowered in everyday life as a direct result of the era of globalization. Such a significant relationship between culture and society makes culture essential for humans, where people cannot leave the culture they already have. All regions almost own the value of local wisdom, and it's just that, in reality, it is scarce to find local knowledge that is empowered in everyday life as a direct result of the era of globalization. Variety of local wisdom, one of which is the art of reog kendang. The research approach is qualitative research. Observation, interviews, and documentation were carried out in the data collection in this study. Data analysis was carried out, namely: Data reduction (data reduction), Data presentation (data display), and Data verification (conclusion drawing/verification). The result of the research is that the actions of students practicing dancing in Reog Kendang for the preservation of local wisdom values are carried out by: They practice dancing diligently, They discuss how to be able to follow dance movements quickly, They play and joke with friends, They get bored quickly if they can't track activities that are considered problematic. In the show, six dancers perform Reog Kendang in groups, each carrying a drum or hotdog. Reog Kendang is often displayed in significant events held in Tulungagung district, East Java. In addition, this dance is also usually performed at various cultural festivals, both at the regional and national levels. Along with the development of this dance, the era began to see many changes, with the addition of various variations in terms of movement, costumes, musical accompaniment, or presentation.